A multi-institution prospective observational study of small bowel obstruction. Issue 3 (September 2015) - Kulvatunyou, Narong; Pandit, Viraj; Moutamn, Sadoun; Inaba, Kenji; Chouliaras, Konstantinos; DeMoya, Marc; Naraghi, Leily; Kalb, Bobby; Arif, Hina; Sravanthi, Reddy; Joseph, Bellal; Gries, Lynn; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND For patients with adhesive small bowel obstruction (ASBO), early surgery after a failed trial of nonoperative treatment can improve outcome. However, deciding which patients require early surgery is difficult, given the lack of specific clinical or radiographic signs. The study goals were to identify clinical and computed tomography (CT) predictors of which patients may need early surgery and to evaluate the utility of the common CT findings. METHODS This was a multi-institution prospective observational study for patients who were admitted with ASBO. Patients were excluded if their SBO were not managed conservative initially; were within 30 days postoperatively; were caused by external hernias, small bowel tumor, or intussusception; and were related to Crohn's disease. Clinical and laboratory variables were collected prospectively. CT findings were interpreted by a blinded designated radiologist. To identify significant predictors, we performed a multivariable regression analysis. RESULTS During 22 months, we enrolled 200 patients with ASBO. Patients' mean (SD) age was 60 (18) years; 50% were male. Fifty-two patients (26%) underwent surgery. Of those who underwent surgery, the median duration of nonoperative treatment was 1.5 days (interquartile range, 1–2.5 days). In the regression model, we identified no flatus (odds ratio [OR], 3.28; 95% confidence interval [CI], 1.51–7.12; p = 0.003), presence of free fluid on CT (OR, 2.59; 95% CI, 1.13–5.90; p = 0.023), and high-grade obstruction by CT (OR, 2.44; 95% CI, 1.10–5.43; p = 0.028) to be significant predictors for ASBO patients who may need early surgery. CONCLUSION In this study, we prospectively derived one clinical and two CT predictors which ASBO patients may benefit from an early surgical intervention. However, a future study to validate these predictors is needed. LEVEL OF EVIDENCE Therapeutic study, level III; prognostic study, level II.